ECOSYSTEM APPROACH TO REEF FISHERIES MANAGEMENT IN WEH ISLAND, NANGROE ACEH DARUSSALAM - Irfan Yulianto; Budy Wiryawan; Am Azbas Taurusman (Indonesian Fisheries Research Journal, 2011)
Fisheries management has been traditionally governed to maximize economic benefit with little concern on its ecological impacts. Food and Agriculture Organization with its Code of Conduct for Responsible Fisheries has played an important role to a fundamental change in the new paradigm of fisheries management, which include ecosystem aspect. The Food and Agriculture Organization has mandated that every country in the world should use this approach. Weh Island is located in AcehProvince that has good coral reef condition and rich in reef fishes, therefore reef fishery is prominent. The objectives of this study are (1) to study the ecological status of reef fish, and (2) to formulate the priority areas as candidates of marine protected areas in Weh Island. Fish catch survey, underwater visual census, and focus group discussion were conducted to collect data. Data analysis used fish biomass, financial analysis, linear goal programming, and marxan analysis. Results of this study successfully identified eight fishing gears operated in Weh Island in artisanal reef fisheries. These fishing gears are gillnet, bottom gillnet, handline, muroami, trolline, speargun, longline, and purseseine. There were 84 species identified as high economic value species and were modelled in this study. Gillnet and bottom gillnet were identified as optimum fishing gears. I.e. Meulee, Anoi Itam, Iboih, Jaboi, and Klah Island were identified as priority areas.